Share on vk Share on google_plusone_share Share on twitter Share on email More Sharing Services The history of the Roman Republic according to the axiological approach: On the problem of the mos maiorum essence - A.O. Kudratov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article analyzes one way to make a theoretical sense of the essence of the Roman civic ethics, a constant element of the political struggle in the Roman Republic. Notably, the axiological approach, which is an important methodological tool due to the specifics of the Roman political practice, has not been used in historiography to its fullest potential due to lack of conceptualization. This is reflected in historiographical studies: most researchers unanimously emphasize the essential role of the Roman virtues (virtutes) in the Roman political culture. The analysis of the historiographical works showed that philological methods are traditionally used to study the Roman virtues, which serve as a key to answering numerous questions related to the ideas of the Romans. The results obtained revealed that these tools are not sufficient themselves due to the discrepancy between the Roman reality and political rhetoric, in the context of which the virtues are identified. Differences were found between Russian and foreign historiography in the approaches to the analysis of the concepts related to the one under consideration here. The vast potential of using the axiological approach to study the Roman history was outlined. Earlier attempts to get the most of it were critically assessed. To advance the achievements that have been made, the concept of value was clarified and defined in terms of the Roman political context.